The Effect of Baseline Ovarian Cyst on Pregnancy Outcomes in Ovulation Induction/Intrauterine Insemination Cycles - Karen Bethel; Rachel Warwar; Suruchi Thakore; Emily G. Hurley (Women's Health Reports)
Objective: To determine the effects of a baseline ovarian cyst on ovulation induction/intrauterine insemination (OI/IUI) cycle outcomes. Methods: A retrospective cohort analysis of 270 patients and 461 OI/IUI cycles performed between 2011 and 2021 was performed. The exposure variable was a simple appearing ovarian cyst diagnosed at baseline ultrasound measuring ≥10 mm with an estradiol level <75 ng/mL. The primary outcome analyzed was an ultrasound-confirmed intrauterine pregnancy. Secondary outcomes included positive pregnancy test and live birth. Summary data were presented with percentages, mean (standard deviation), or median (interquartile range). Comparisons of dichotomous variables were performed with the chi-square test, and continuous variables were compared using t-test. Regression analysis was performed using a general linear model. p-Values <0.05 were considered statistically significant. Results: The clinical pregnancy rate was nominally higher in the group without a cyst present at baseline ultrasound compared with those cycles with a simple cyst present, but the difference was not statistically significant (45/300 [15%] vs. 15/161 [9.3%], risk ratio [RR] 0.63 [0.36, 1.1]). After adjusting for BMI ≥30 and age ≥35, there remained no significant difference in clinical pregnancy rate (adjusted RR 0.65 [0.37, 1.1]). Conclusion: Given the present data, it is reasonable to proceed with IUI in the case of a baseline simple ovarian cyst. However, this finding may have an impact on clinical pregnancy outcomes in OI/IUI, and further research on the topic is warranted. Although this study was underpowered with fewer cycles than needed to demonstrate a significant difference, the point estimate suggests that the difference in clinical pregnancy rate could be ∼35%.